ANALISIS BAHAYA KESELAMATAN DAN KESEHATAN KERJA DI INSTALASI LAUNDRY RSUD dr. SOERATNO GEMOLONG - Hasfi Rahmah Wati; Wahyu Rizky; Fifi Alviana (Jurnal Ilmiah Kesehatan, 2025)
The main function of a laundry installation is to maintain the cleanliness and sterilization of linen and patient clothing used in daily medical activities. Workers in laundry facilities are potentially exposed to a variety of hazards, including physical, chemical, biological, ergonomic and psychosocial hazards. The implementation of Occupational Safety and Health (K3) is a form of effort to create a safe, healthy workplace so that it can reduce and be free from work accidents., The purpose of this study is to determine occupational safety and health hazards in the laundry installation of the Regional General Hospital dr. Soeratno Gemolong. This study uses a descriptive method with a qualitative approach. This research was conducted at the dr. Soeratno Gemolong Regional General Hospital in January – February 2025., The method used in this study was conducted by interviewing the head of  the laundry installation  section and the laundry officer., the results of the study show that in the laundry installation  of dr. Soeratno Hospital, the main obstacles faced are the lack of washing machine equipment, human resources do not yet have a decree, provide adequate infrastructure, and make special SOPs for laundry installation.